2008
DOI: 10.1111/j.1399-3054.2008.01160.x
|View full text |Cite
|
Sign up to set email alerts
|

Ozone‐induced changes in photosynthesis and photorespiration of hybrid poplar in relation to the developmental stage of the leaves

Abstract: Young poplar trees (Populus tremula Michx. x Populus alba L. clone INRA 717-1B4) were subjected to 120 ppb of ozone for 35 days in phytotronic chambers. Treated trees displayed precocious leaf senescence and visible symptoms of injury (dark brown/black upper surface stippling) exclusively observed on fully expanded leaves. In these leaves, ozone reduced parameters related to photochemistry (Chl content and maximum rate of photosynthetic electron transport) and photosynthetic CO(2) fixation [net CO(2) assimilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 77 publications
(89 reference statements)
4
56
1
Order By: Relevance
“…Under drought conditions, the impairment of CO 2 assimilation causes an imbalance between the electron transport rate in the photosynthetic electron transport (PET) chain and the plant's capacity to utilize NADPH (reduced nicotinamide adenine dinucleotide phosphate) and ATP (adenosine tri-phosphate) in the Calvin cycle (Chaves et al, 2009). Under this CO 2 -limiting condition, photorespiration is proposed as an important alternative pathway for consuming the excess reducing equivalents from the photochemical reactions, avoiding photoinhibition (Bagard et al, 2008;Takahashi and Badger, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under drought conditions, the impairment of CO 2 assimilation causes an imbalance between the electron transport rate in the photosynthetic electron transport (PET) chain and the plant's capacity to utilize NADPH (reduced nicotinamide adenine dinucleotide phosphate) and ATP (adenosine tri-phosphate) in the Calvin cycle (Chaves et al, 2009). Under this CO 2 -limiting condition, photorespiration is proposed as an important alternative pathway for consuming the excess reducing equivalents from the photochemical reactions, avoiding photoinhibition (Bagard et al, 2008;Takahashi and Badger, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The estimation of the photorespiratory rate (P R ) was determined as described in Bagard et al (2008) from the measurements of gas exchange (P N and R d ) and chlorophyll a fluorescence-derived ETR parameter by the equation:…”
Section: Gas Exchange Measurementsmentioning
confidence: 99%
“…At the canopy level, ambient O 3 concentrations caused reductions in both light-saturated photosynthesis rate (A sat ) and g s of the lower canopy that were about 30% more than those of the upper canopy in black poplar (Populus nigra L.) species (Novak et al, 2005). Young poplar trees also showed that reduced photosynthetic parameters related to chlorophyll content, maximum rate of photosynthetic electron transport and net photosynthetic assimilation appeared only on fully expanded leaves, but not on young and undeveloped leaves, which was partly attributed to differences in leaf anatomy between expanding and fully expanded leaves (Bagard et al, 2008). Similarly, for an evergreen broad-leaved species, Castanaopsis sieboldii, elevated O 3 significantly reduced the net photosynthetic rate of previous-year leaves but not that of expanding current-year leaves (Watanabe et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…For hybrid poplar and Aspen, elevated O 3 concentrations altered the patterns of change in leaf area, photosynthetic rate and carbon gain with leaf position from root to apex and the older leaves were more sensitive to O 3 than younger leaves (Bagard et al, 2008;Greitner et al, 1994). At the canopy level, ambient O 3 concentrations caused reductions in both light-saturated photosynthesis rate (A sat ) and g s of the lower canopy that were about 30% more than those of the upper canopy in black poplar (Populus nigra L.) species (Novak et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation